Tremelimumab plus durvalumab versus sorafenib in first-line treatment of unresectable hepatocellular carcinoma: a cost-effectiveness analysis from the US payer perspective - Bin Li; Shuqiao Cheng; Jian Xiao; Shao Liu; Lanhua Tang (BMJ Open)
Objective In a recently published 4-year overall survival (OS) update from the phase III clinical trial named HIMALAYA (NCT03298451), single tremelimumab plus regular interval durvalumab (a regimen termed STRIDE) demonstrated significantly improved OS compared with sorafenib in the first-line setting of unresectable hepatocellular carcinoma (uHCC). Although dual immunotherapy represents a novel treatment option for uHCC, the economic implications of these high-priced drugs require further exploration. This study aimed to evaluate the cost-effectiveness of STRIDE in uHCC to inform first-line treatment decisions and help allocate medical resources most effectively.Design Using a partitioned survival model, we conducted a cost-effectiveness analysis comparing STRIDE to sorafenib in the first-line treatment of uHCC. Clinical information was gathered from the phase III HIMALAYA trial. Costs and health state utilities data were derived from previous literature. Uncertainty of the model was assessed through one-way sensitivity analysis and probabilistic sensitivity analysis.Outcome measures Total costs, life years, quality-adjusted life years (QALYs), incremental QALYs and incremental cost-effectiveness ratio (ICER).Setting US payer perspective.Participants 393 participants in the STRIDE group and 389 participants in the sorafenib group who were diagnosed with uHCC and had no previous systemic treatment.Interventions Single-dose tremelimumab plus monthly durvalumab (STRIDE) versus sorafenib.Results Treatment with STRIDE provided an additional 0.51 QALYs at an incremental total cost of United States dollar ($)9812. The ICER of STRIDE was $19 239 per QALY compared with sorafenib, which falls below the willingness-to-pay threshold of $150 000 per QALY. Sensitivity analyses indicated that our results were robust to the variation ranges of key inputs.Conclusion In this economic evaluation comparing two first-line systemic therapies for uHCC patients, STRIDE was cost-effective compared with sorafenib from a US payer perspective. Our study is the first to demonstrate that immunotherapy can provide both survival benefits and economic viability in uHCC.